A Contingency Theory Approach to Understanding Small Retail Business Continuity During COVID‐19. (14th February 2022) - Childs, Michelle; Turner, Tom; Sneed, Christopher; Berry, Ann
Abstract : Small retail businesses are particularly vulnerable to turbulence caused from the COVID‐19 pandemic. To consider what actions retailer owners/managers can take to maneuver during such trying times, this study investigated leadership qualities associated with managing during times of crisis. Through in‐depth interviews with 12 small retail leaders, thematic data analysis revealed an emergence of contingent leadership, including an internal focus on cash flow and employees and an external focus on preserving key stakeholder relationships. Retail leaders displayed a resilient mindset, showing passion, agility, innovation, and relationship development. A conceptual model is proposed to further illustrate findings from the study.